The Whitening, Moisturizing, Anti-aging Activities, and Skincare Evaluation of Selenium-Enriched Mung Bean Fermentation Broth - Wei, Kang; Guo, Congyin; Zhu, Jiangxiong; Wei, Yang; Wu, Meirong; Huang, Xiaodong; Zhang, Mu; Li, Jide; Wang, Xueyun; Wang, Yuanfeng; Wei, Xinlin (Frontiers in Nutrition, 2022)
Selenium-enriched mung bean (Se-MB) was a combination of mung bean (MB) and selenium (Se), which have a variety of potential biological activities. However, little is known about the skincare activity of Se-MB. The chemical composition of Se-MBFB was analyzed to investigate the whitening, moisturizing and anti-aging activities of Se-MB fermentation broth (Se-MBFB). The tyrosinase inhibition, anti-melanogenic in melanocytes (B16F10 cells) and moisturizing effect in human dermal ﬁbroblasts (HDFs) were analyzed. Besides, the free radical scavenging activity of Se-MBFB were assessed in vitro. In order to verify the in vivo effects and the potential of practical applications of Se-MBFB, a clinical trial was conducted in the participants of 31 Chinese women aged 25–60 years, with no pigmentation disorder, no illness, no history of hypersensitivity reaction, and no use of skincare product on the face. The participants used a Se-MBFB masque for 15-20 min after cleaning face. The measurement points were week 0, 2, and 4 (W0, W2, and W4) after using the masque, and target sites were cheek and canthus. The following parameters were recorded on the target sites at each visit: melanin index, skin color, cuticle moisture content, transepidermal water loss and crow's feet. The results demonstrated that Se-MBFB was rich in polyphenols, peptides and γ-aminobutyric acid (GABA), displayed signiﬁcant free radical scavenging and tyrosinase inhibiting activities, decreased the synthesis of melanin, and upregulated the aquaporin-3 (AQP3) expression. The test of Se-MBFB mask showed that after 4 weeks of using the Se-MBFB facemask, the faces of the participants became whiter with reduced wrinkles and increased moisture content. Se-MB possessed the excellent whitening, moisturizing and antioxidant efficacy, which could lay a scientific foundation for utilization and development of skincare products of Se-MB and its related industrial cosmetics products.